Autologous mitochondrial transplantation in male mice as a strategy to prevent deleterious effects of peripheral ischemia-reperfusion - Boutonnet, Lauréline; Mallard, Joris; Charles, Anne-Laure; Hucteau, Elyse; Geny, Bernard; Lejay, Anne; Grandperrin, Antoine (American Journal of Physiology: Cell Physiology, 2024)
: Ischemia-reperfusion (IR) is known to induce severe tissue damage, notably through mitochondrial dysfunction. Mitochondrial transplantation has emerged as a promising therapeutic strategy in cardiac IR, however few studies have previously assessed its efficacy in the context of peripheral IR. Therefore, the objective of this study was to assess the effect of mitochondrial transplantation in a hindlimb model of IR injury. : Thirty-six SWISS mice were divided into three groups: control (CTL, n=12), ischemia-reperfusion (IR, n=12) and IR with mitochondrial transplantation (MT, n=12). Ischemia (2 hours) was induced using the tourniquet model, around the right hind limb in IR and MT groups. In MT group, mitochondria isolated from the right rectus muscle, a non-ischemic region, were injected shortly before reperfusion. Mitochondrial respiration, calcium retention capacity and western blotting analysis were performed 2 hours after reperfusion. : Compared to CTL group, IR led to a decrease in the mitochondrial respiratory capacity, particularly for the basal state (-30%; p=0.015) and the oxidative phosphorylation (-36%; p=0.024), as well as calcium retention capacity (-45%; p=0.007). Interestingly, mitochondrial transplantation partially restored these functions since no difference between MT and CTL groups were found. Additionally, the administration of healthy mitochondria resulted in a positive regulation of redox balance and mitochondrial dynamics within the skeletal muscle. : While further investigations are needed to better characterize underlying mechanisms, mitochondrial transplantation represents a promising strategy in the setting of IR-induced muscular damage.